PP7 Using in situ simulation to manage changes to an emergency department's processes during the COVID-19 pandemic. (10th November 2020) - Blackmore, Andrew; Herrieven, Elizabeth; Stewart, Paul; Cherian, Biju
Abstract : Background: The first positive COVID-19 tests in the UK were in our Trust. We were fortunate that there was a significant time delay between the first identified cases and the surge in cases that was seen across the UK in early 2020. Our department had been designed for maximal ease of access to equipment but the pandemic required us to change our layout and pathways. Summary of Work: Across our adult and paediatric emergency departments we used targeted simulation scenarios to train staff, to help in the design of new pathways and expose latent errors. A series of basic scenarios with a member of staff as a simulated patient were used to train existing and redeployed staff in basic skills such as donning/doffing, entering and exiting a barriered room and passing samples out of the room without cross-contamination. Another series of simulated patient scenarios were used to train clinicians in the clinical management of a COVID-19 patient with an escalating oxygen requirement. We also practiced transfer of a deteriorating patient to Resus. Other simulation scenarios used an intubatable manikin to practice scenarios involving aerosol generating procedures. ED intubation simulations contributed to the design of our Trust's COVID-19 intubation checklist. We ran simulated cardiac arrest scenarios in adult and paediatric Majors cubicles and in Resus. In situ simulations were used to design our new 'Cold Majors' area in what was our Emergency Care Area. We designed scenarios to test transfer pathways from the ambulance bay to the new area and from Cold Majors to X ray and CT. Summary of Results: In all, more than 50 scenarios were run over a six week period. Orientation simulations ran most frequently and highlighted any lapses in infection control practices that could be addressed. Deteriorating patient, intubation, cardiac arrest and fitting patient scenarios highlighted latent errors around storage of equipment and preparation of airway trollies. They also directly informed the new layout of our resus cubicles and the ever-evolving departmental COVID-19 policies. In Cold Majors, they helped to plan the flow of patients within the new area and helped to orientate staff within the new environment. Discussion and Conclusions: In situ simulation is an effective tool to help an emergency department adapt to the new demands placed on it by the COVID-19 pandemic; from maintaining standards in infection control to designing pathways and even the layout of the department itself.